Vitalizing organizational justice in mediating effect of good corporate governance on teacher’s organizational citizenship behavior - Widodo Widodo; Sulistiasih Sulistiasih (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study analyzes the effect of good corporate governance (GCG) on teacher’s organizational citizenship behavior (OCB) mediated by organizational justice. The research data was collected by a questionnaire: GCG, organizational justice, and OCB, through the survey methods toward 356 teachers of State Junior High School in Indonesia. Data analysis uses path analysis supported by descriptive statistics and correlational. The results show that GCG had a significant effect on OCB mediated by organizational justice. This study also was found a fit research model about the GCG’s affects teacher’s OCB mediated by organizational justice. This new model can discuss among researchers and practitioners. Furthermore, this new model can be discussed as a reference among researchers and practitioners to develop better models of teacher’s OCB in the future and various contexts of educational organizations.